2015
DOI: 10.1098/rsif.2015.0168
|View full text |Cite
|
Sign up to set email alerts
|

Isotropic microscale mechanical properties of coral skeletons

Abstract: Scleractinian corals are a major source of biogenic calcium carbonate, yet the relationship between their skeletal microstructure and mechanical properties has been scarcely studied. In this work, the skeletons of two coral species: solitary Balanophyllia europaea and colonial Stylophora pistillata, were investigated by nanoindentation. The hardness H IT and Young's modulus E IT were determined from the analysis of several load -depth data on two perpendicular sections of the skeletons: longitudinal ( parallel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
26
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(42 citation statements)
references
References 36 publications
11
26
5
Order By: Relevance
“…S4, 0.119% to 0.098% for the (111) reflection). Although the crystallite size varies in each method, the values calculated for pH 8.2 sample are consistent with the nanocrystal size observed in S. pistillata by AFM 4,41 . The variation in crystallite size is the same for the planes (111) and (021) and they have a comparable slope to Rietveld calculations (Fig.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…S4, 0.119% to 0.098% for the (111) reflection). Although the crystallite size varies in each method, the values calculated for pH 8.2 sample are consistent with the nanocrystal size observed in S. pistillata by AFM 4,41 . The variation in crystallite size is the same for the planes (111) and (021) and they have a comparable slope to Rietveld calculations (Fig.…”
Section: Resultssupporting
confidence: 82%
“…These parameters are not prone to change due to decomposition of intraskeletal organic matter during diagenesis 53 , thus may become a new crystallographic tool for detecting OA in well preserved aragonitic fossil corals supporting other well established geochemical tools e.g., boron isotopes 54 . In the long run (colony life span) crystallo-chemical changes may scale up at higher levels of skeletal hierarchy and potentially affect biomechanical properties of the reef structure 41 .…”
Section: Discussionmentioning
confidence: 99%
“…With regard to skeletal stiffness and hardness, our data were comparable to those recorded in shallow-water zooxanthellate corals around localised volcanic acidification sites with low pH conditions (Fantazzini et al, 2015;Pasquini et al, 2015), where Fantazzini et al (2015) reported an ∼8% difference in stiffness but no difference in hardness over 0.4 pH points. While similar, results are not directly comparable to CWC investigated here due to the higher aragonite saturation ( Arag > 1) of the volcanic sites used, and the zooxanthellate nature of the shallow corals.…”
Section: Mechanical and Mineral Properties Of Cwc Skeletonssupporting
confidence: 83%
“…These studies were conducted on the upper most part of coral skeletons from pristine, oligotrophic reefs. However, as suggested by Pasquini et al (2015), corals from a wider range of environments with differing organic matrix content and porosity may have distinct mechanical properties.…”
Section: Introductionmentioning
confidence: 95%
“…However, the role of organic content on the overall strength of hard corals is complex, with no straightforward correlation between organic content and mechanical durability (Amini and Miserez 2013). In scleractinian corals, reported values for organic matrix content vary from 1 to 3% (Cuif et al 2004;Dauphin et al 2006;Falini et al 2015;Pasquini et al 2015). These studies were conducted on the upper most part of coral skeletons from pristine, oligotrophic reefs.…”
Section: Introductionmentioning
confidence: 99%